PENGARUH LATIHAN FISIK (SENAM JANTUNG SEHAT) TERHADAP KADAR RESISTIN DAN KADAR GULA DARAH PADA OBESITAS - Nunung Sri Mulyani; Yulia Fitri; Ramlan Silaban; Zulfahri Zulfahri (Jurnal Pendidikan Kimia (JPKim), 2014)
AbstractObesity is a global epidemiology and serious healthy treat due to morbidity and mortality raised. On the whole of the adult population in the world get obese 7.7% in men and 11.9% in women. Adipose tissue accumulates on obesity functioning as endocrine gland secrets all sitokin and peptide hormones. The secretion of those sitokin and hormones play role in controlling body weight balancing and energy metabolism. Resistin an adipositokin (adipokin) secreted by  adiposit that assumes to have important role as circuit between adiposity and insulin resistance. Physical exercises could influence resistin levels and blood sugar on obesity. This research aims to identify the influence of physical exercises ((healthy heart gym) of resistin and blood sugar levels on obesity. The design of this research uses purposive sampling. The subject of the study 25 female students of 18-21 years of age of Poltekkes Nutrition Department Kemenkes Aceh. Gymnastic exercise program done with a healthy heart with a frequency of 5 times a week for 4 weeks with intensity 30 minutes. The result of pre and post resistin levels checked is analyzed both descriptively and inferentially by t test and correlation (moment/pearson).   The result of t test of and correlation found that; there is no influence physical exercises toward resistin levels at the people with obesity (p= 0, 45), there is influence physical exercises (healthy heart gym) toward blood sugar levels of the people with obesity. (p=0, 03), there is no significant influences between resistin levels and blood sugar levels of the people with obesity in pre and posttest (p=0, 26). Based on the finding above, we may conclude that the physical exercises (healthy heart gym) influences toward blood sugar levels, but it doesn’t toward resistin levels.Keywords : Obesity, Resistin, blood sugar levels, physical exercises (healthy heart gym)